Assessment of the invasive potential of Foeniculum vulgare (fennel) in the Sarah Baartman District and Nelson Mandela Bay Municipalities in South Africa`s Eastern Cape Province - Magagula, Thokozane Innocent Pappa (My University, 2018)
Foeniculum vulgare (Fennel) is native and widely distributed in many Mediterranean countries in Europe. Nowadays the species' distribution extends globally due to its cultivation as a food crop and its use as an herb. Fennel has been reported as invasive in Australia, New Zealand and California and reported as a naturalised garden escapee in South Africa. Because of similarities between the climates of the Western Cape Province in South Africa and Mediterranean countries the likelihood of the species becoming invasive in South Africa is high. In this report, the Sarah Baartman District and Nelson Mandela Bay Municipalities in the Eastern Cape Province, South Africa, were used as study areas to assess the invasive potential of Fennel. To this end, information from different sources was used to draw conclusions on the species' invasiveness in South Africa. These included using ArcGIS maps to estimate the current distribution of fennel in the study area and South Africa with the use of survey records, Herbarium data and SAPIA information; CLIMEX modelling to estimate the future potential distribution of the species based on climatic suitability; an assessment of major vegetation types where the species mostly occur; seed germination and reproductive output; and a risk assessment. A comparison of current distributional data with predicted future distribution of the species found that South Africa has a suitable climate for fennel and therefore the likelihood of the species establishing in many regions is high. Anthropogenic activities are anticipated to increase the potential of the species to become invasive. This conclusion is based on the observation that where vegetation has been degraded as a result of human influence, naturalised populations of the species were observed. High seed production capacity and high germination rates of Fennel also increase the likelihood of the species spreading now and in the future. The species also obtained high weed risk assessment score in South Africa, and swift action is required to control the species while populations are still manageable in size and before the species has a significant environmental impacts. Delayed action v will result in the continued spread of this invasive species, making it more difficult to successfully curb the spread thereof in the future
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Masters of Science by Coursework and Research Report, Johannesburg 2018
Keywords: Seeds--Development; Germination